(3b 5) (-2b-5) (b-4)

I assume this question would be:

= (3b + 5) + (-2b - 5) + (b - 4)

= 3b +5 -2b - 5 + b - 4

= 3b -2b + b + 5 - 5 - 4

= 2b - 4

2b = 4

b = 4/2

b = 2

Please post complete question if my assumption is not true. I am available to assist you in your academic courses.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up